Evaluasi Dampak E-Samsat dan Sanksi Untuk Kegagalan Membayar Pajak - Sendi Ardian Tampubolon; Shirley Wijaya; Kristi Indriyani (CV. Ulil Albab Corp, 2025)
The current study explores the impact of E-SAMSAT implementation and administrative sanctions regarding taxpayer compliance for motor vehicles in Bekasi Regency, Indonesia. Despite a growing number of registered vehicles, many taxpayers remain noncompliant due to bureaucratic hurdles and limited service access. E-SAMSAT was introduced to simplify the payment process and improve compliance levels. The research employed a quantitative explanatory approach using purposive sampling. One hundred responders in all were chosen from among the motor vehicle taxpayers. Questionnaires were used to gather data, and SPSS version 25 was used for analysis. The analysis comprised hypothesis testing, traditional assumption testing, and validity and reliability testing. According to the study, administrative punishment and the adoption of E-SAMSAT both significantly and favorably affect taxpayer compliance. E-SAMSAT increases accessibility and convenience, encouraging timely payments, while administrative sanctions serve as a deterrent to late compliance. The regression model explains 50.9% of the variance in taxpayer compliance behavior, indicating a strong influence from both independent variables.